The Role of Growth Hormone on Ovarian Functioning and Ovarian Angiogenesis - Devesa, Jesús; Caicedo, Diego (Frontiers in Endocrinology, 2019)
Although not yet well understood, today it is clear that Growth Hormone (GH) exerts a relevant role in the regulation of ovulation and fertility; in fact, fertility is lower in women with GH deficiency (GHD), and GH receptors (GHR) and GH mRNA have been found in the ovary since the onset of follicular development in humans. However, despite the strong evidence of GH in the regulation of fertility, many aspects of GH actions at this level are still not well established, and it is likely that some controversial data depend on the species analyzed, the dose of the hormone and the duration of use of GH. Folliculogenesis, ovulation, and corpus luteum formation and maintenance are processes that are critically dependent on angiogenesis. In the ovary, new blood vessel formation facilitates oxygen, nutrients, and hormone substrate delivery, and also secures transfer of different hormones to targeted cells. Some growth factors and hormones overlap their actions in order to control the angiogenic process for fertility. However, we still know very little about the factors that play a critical role in the vascular changes that occur during folliculogenesis or luteal regression. To promote and maintain the production of VEGF-A in granulosa cells, the effects of local factors such as IGF-I and steroids are needed; that VEGF-A-inducing effect cannot be induced by luteinizing hormone (LH) or chorionic gonadotropin (CG) alone. As a result of the influences that GH exerts on the hypothalamic-pituitary-gonadal axis, facilitating the release of gonadotropins, and given the relationship between GH and local ovarian factors such as VEGF-A, FGF-2, IGF-1 or production of sex steroids, we assume that GH has to be a necessary factor in ovarian angiogenesis, as it happens in other vascular beds. In this review we will discuss the actions of GH in the ovary, most of them likely due to the local production of the hormone and its mediators.